Binjai city residents' preferences for investing in gold at the Binjai Outlet Sharia Pawnshop Agent - Yasmin Nazwa; Elida Elfi Barus (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study examines the preferences of Binjai City residents for investing in gold at the Pegadaian Syariah Outlet Binjai, influenced by various factors such as economic, religious, social, ease of service, and financial literacy levels. Gold investment is viewed as a safe, stable instrument capable of protecting asset value from inflation, making it increasingly popular among various groups, including the younger generation. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation of customers and Pegadaian Syariah. The results show that the increasing public interest in investing in gold is not only driven by economic benefits, but also by a sense of security, trust in sharia institutions, and easy access to the services offered. Furthermore, Pegadaian Syariah plays a significant role in improving public financial literacy through gold savings products that can be started with small capital and a system that complies with sharia principles. However, obstacles remain, such as a low understanding of the gold investment mechanism among some residents and suboptimal socialization. Thus, it can be concluded that the preference of the people of Binjai City in investing in gold is the result of the interaction of various factors that influence each other and indicate a change in the pattern of people's economic behavior towards a more productive and sharia-based direction.